ANALISIS PENGARUH PERLAKUAN PANAS TERHADAP PELAT KLASIFIKASI BKI TEBAL 10 mm PADA SAMBUNGAN LAS - Mulyatno, Imam Pujo; Yudo, Hartono (Department of Naval Architecture - Diponegoro University, 2008)
Heating treatment at the fabrication make the tensile strength, bending strength, and hardness strength are become lower. The research vision are to prover that heating at the plate without heating treatment, heating treatment 300 0C, heating treatment 600 0C. Welding at research use SMAW (Shield Metal Arc Welding) welding method. The mean of tensile test without heating treatment (419 Kg/mm2), heating treatment 3000C (424 Kg/mm2), heating treatment 6000C (415 Kg/mm2). The mean of bending test without heating treatment (845 N/mm2), heating treatment 3000C (768 N/mm2), heating treatment 6000C (724 N/mm2). The mean of hardness test whitout heating treatment (129 HVN), heating treatment 3000C (147 HVN), heating treatment 6000C (160 HVN). From the test we get conslusion that the best result is Marine use plate ST 42 with BKI classification with heating treatment 300 0C, heating process is 60 minutes in the oven. After that cooling treatment to be done until back normal degree